Outcomes of Trabeculo-Descemet’s Membrane Microperforation During Combined Phacoemulsification and Deep Sclerectomy - Mahdi Sharifzadeh Kermani; Sana Jalalmanesh; Hesam Fat'hi-zadeh; Ali Sharifi; Amin Zand (Journal of Ophthalmic & Vision Research, 2025)
Purpose: To evaluate the impact of inadvertent intraoperative microperforation of the trabeculo- Descemet’s membrane (TDM) on postoperative outcomes in cases with cataract and either primary open-angle glaucoma (POAG) or pseudoexfoliative glaucoma (PEXG) during combined phacoemulsification and deep sclerectomy (PDS). Methods: In this prospective case–control study, 73 eyes of 73 patients with cataract and POAG/PEXG who underwent PDS were enrolled. Patients were divided into two groups based on the presence or absence of inadvertent intraoperative TDM microperforation. The primary outcome measures included intraocular pressure (IOP), number of antiglaucoma drugs, and assessment of adverse effects during a six-month follow-up period. Results: Significant decreases in IOP were observed at all follow-up time points (day 7, month 1, and month 6) in both groups compared to baseline (P < 0.001). No significant differences in IOP were found between the groups at any time point, except on day 7, while the perforation group exhibited a significantly lower IOP compared to the non-perforation group (11.84 ± 4.78 vs 14.03 ± 2.50 mmHg, P = 0.017). At month 6, the mean number of antiglaucoma drugs was 0.19 ± 0.46 in the perforation group and 0.06 ± 0.23 in the non-perforation group, suggesting a significant reduction in both groups compared to baseline (P < 0.001) with no statistically significant difference between the two groups (P = 0.124). Hypotony was observed in 3 (8.1%) eyes with perforation, but it resolved without persistent complications in subsequent follow-ups. Conclusion: Inadvertent TDM microperforation during PDS for POAG or PEXG did not impact IOP outcomes compared to non-perforated cases over a six-month period, nor did it increase the incidence of complications.